2020
DOI: 10.1021/acsenergylett.0c01445
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Activated Corrosion in Tin–Lead Halide Perovskite Solar Cells

Abstract: Mixed tin–lead halide perovskite solar cells have promising power conversion efficiencies, but long-term stability is still a challenge. Herein we examine the stability of a 60:40 tin–lead perovskite to better understand diminished device performance upon thermal treatment, both in ambient and inert atmosphere. Operando X-ray diffraction shows a stable bulk structure of the perovskite absorber, leading to the hypothesis that surface chemistry dominates the degradation mechanism. X-ray photoelectron spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 46 publications
5
89
0
Order By: Relevance
“…Furthermore, previous studies have suggested that the incorporation of anions with electronegativity stronger than that of I − raises the V Sn formation energy during perovskite crystallisation, further reducing the hole concentration 24,42 . Additionally, for both the I-pristine and I/Br samples, a small shoulder peak appeared at a low binding energy (~485.4 eV), which is ascribed to under-coordinated Sn with an oxidation state of δ < 2 + (Sn δ< 2+ ) 43 . However, this shoulder peak was undetectable in both the I/Cl and I/Br/Cl samples, indicating well-coordinated Sn sublattices and reduced structural imperfections.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies have suggested that the incorporation of anions with electronegativity stronger than that of I − raises the V Sn formation energy during perovskite crystallisation, further reducing the hole concentration 24,42 . Additionally, for both the I-pristine and I/Br samples, a small shoulder peak appeared at a low binding energy (~485.4 eV), which is ascribed to under-coordinated Sn with an oxidation state of δ < 2 + (Sn δ< 2+ ) 43 . However, this shoulder peak was undetectable in both the I/Cl and I/Br/Cl samples, indicating well-coordinated Sn sublattices and reduced structural imperfections.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to perovskite single junction [ 13,14,16,17,24 ] and perovskite/CIGS [ 18 ] tandem solar cells that use well‐studied compositionally stable radiation‐hard perovskite absorber compositions [ 10,12,15–17 ] with a bandgap of ≈1.6 eV, the high‐gap and low‐gap perovskite compositions required for all‐perovskite tandem PV thus face additional potential degradation issues under harsh radiation conditions. The phase‐separation of mixed perovskites with high bandgap as well as the oxidation of Sn 2+ to Sn 4+ in low‐gap perovskites is known to be triggered by intense and/or prolonged illumination, [ 22,25 ] heat [ 26 ] or γ‐irradiation. [ 27 ] Harsh particle irradiation excites both, the nuclear and electronic subsystems, [ 28 ] and thus heat as well as charge‐induced degradation mechanisms are likely triggered.…”
Section: Potential Of All‐perovskite Tandem Photovoltaics For Spacementioning
confidence: 99%
“…Moreover, recent reports on thermal degradation of PEDOT:PSS/low‐gap perovskite systems have shown that PEDOT:PSS can cause the oxidation of Sn of the low‐gap Pb‐Sn alloyed perovskite, likely activated from the surface. [ 26,81 ] Therefore, in the specific architecture and as shown in Figure 6, the damaged recombination layer may lead to a barrier to charge quenching from the high‐gap perovskite to the C 60, thus increasing the PL intensity of that absorber relative to the pristine control, while the damaged, more‐conductive PEDOT will better quench the PL from the low‐gap cell (cf. Figure 4a).…”
Section: Comparing Radiation‐induced Damage In Iii–v On Ge 3j and Perovskite 2j Pvmentioning
confidence: 99%
“…[ 79,80 ] Substitution of lead (Pb) by tin (Sn) in the B‐site of the perovskite lattice further narrowed the energy gap from 1.31 to 1.1 eV (Figure 2d), with a PCE of ≈12% for Pb:Sn = 1:1. [ 81–85 ] Even though pure tin‐based halide has a narrower energy gap compared with its lead‐based counterpart, with the highest PCE recorded at 12.4%, the stability needs to be further improved for commercialization. [ 86–88 ]…”
Section: A Brief Overview Of Pscsmentioning
confidence: 99%
“…[79,80] Substitution of lead (Pb) by tin (Sn) in the B-site of the perovskite lattice further narrowed the energy gap from 1.31 to 1.1 eV (Figure 2d), with a PCE of %12% for Pb:Sn ¼ 1:1. [81][82][83][84][85] Even though pure tin-based halide has a narrower energy gap compared with its lead-based counterpart, with the highest PCE recorded at 12.4%, the stability needs to be further improved for commercialization. [86][87][88] Other than flexibility in energy gap tuning, ambipolar transport properties of halide perovskite materials have also attracted considerable attention for applications other than PVs.…”
Section: A Brief Overview Of Pscsmentioning
confidence: 99%